ผลการจัดกิจกรรมการเรียนรู้คณิตศาสตร์ตามแนวคิดห้องเรียนกลับทางร่วมกับ การเรียนรู้เชิงรุกที่มีต่อความสามารถในการแก้ปัญหาคณิตศาสตร์และ ความสามารถในการคิดอย่างมีวิจารณญาณของนักเรียนมัธยมศึกษาปีที่ 5 - วิบุลศิลป์, กิตติพันธ์; ละออปักษิณ, จิณดิษฐ์ (An Online Journal of Education, 2018)
The purposes of this study were to 1) Compare mathematical problem solving and critical thinking abilities of eleventh grade students before and after being taught by organizing mathematics learning activities using the flipped classroom approach and active learning. 2) Compare mathematical problem solving and critical thinking abilities of eleventh grade students after being taught by organizing mathematics learning activities using the flipped classroom approach and active learning with the 70 percent criterion. The subjects were eleventh grade students of Sa-nguan Ying School in Suphan Buri, Thailand in the first semester of the academic year 2017. There were 30 students in an experimental group. The results of the research revealed that 1) The mathematical problem solving and critical thinking abilities of student being taught by organizing mathematics learning activities using the flipped classroom approach and active learning were statistically higher than those before learning at the .05 level of significance. 2) The mathematical problem solving and critical thinking abilities of student being taught by organizing mathematics learning activities using the flipped classroom approach and active learning were statistically lower than 70 percent criterion at the .05 level of significance.